Socioeconomic and Racial Determinants of Brachytherapy Utilization for Cervical Cancer: Concerns for Widening Disparities. Issue 12 (December 2021) - Boyce-Fappiano, David; Nguyen, Kevin A.; Gjyshi, Olsi; Manzar, Gohar; Abana, Chike O.; Klopp, Ann H.; Kamrava, Mitchell; Orio, Peter F.; Thaker, Nikhil G.; Mourtada, Firas; Venkat, Puja; Chang, Albert J.
Abstract : PURPOSE: Cervical cancer (CC) disproportionately affects minorities who have higher incidence and mortality rates. Standard of care for locally advanced CC involves a multimodality approach including brachytherapy (BT), which independently improves oncologic outcomes. Here, we examine the impact of insurance status and race on BT utilization with the SEER database. MATERIALS AND METHODS: In total, 7, 266 patients with stage I-IV CC diagnosed from 2007 to 2015 were included. BT utilization, overall survival (OS), and disease-specific survival (DSS) were compared. RESULTS: Overall, 3, 832 (52.7%) received combined external beam radiation therapy (EBRT) + BT, whereas 3, 434 (47.3%) received EBRT alone. On multivariate logistic regression analysis, increasing age (OR, 0.98; 95% CI, 0.98 to 0.99; P < .001); Medicaid (OR, 0.80; 95% CI, 0.72 to 0.88; P < .001), uninsured (OR, 0.67; 95% CI, 0.56 to 0.80; P < .001), and unknown versus private insurance (OR, 0.61; 95% CI, 0.43 to 0.86; P < .001); Black (OR, 0.68; 95% CI, 0.60 to 0.77; P < .001) and unknown versus White race (OR, 0.30; 95% CI, 0.13 to 0.77; P = .047); and American Joint Committee on Cancer stage II (OR, 1.07; 95% CI, 0.93 to 1.24; P = .36), stage III (OR, 0.82; 95% CI, 0.71 to 0.94; P = .006), stage IV (OR, 0.30; 95% CI, 0.23 to 0.40; P < .001), and unknown stage versus stage I (OR, 0.36; 95% CI, 0.28 to 0.45; P < .001) were associated with decreased BT utilization. When comparing racial survival differences, the 5-year OS was 44.2% versus 50.9% ( P < .0001) and the 5-year DSS was 55.6% versus 60.5% ( P < .0001) for Black and White patients, respectively. Importantly, the racial survival disparities resolved when examining patients who received combined EBRT + BT, with the 5-year OS of 57.3% versus58.5% ( P = .24) and the 5-year DSS of 66.3% versus 66.6% ( P = .53) for Black and White patients, respectively. CONCLUSION: This work demonstrates notable inequities in BT utilization for CC that particularly affects patients of lower insurance status and Black race, which translates into inferior oncologic outcomes. Importantly, the use of BT was able to overcome racial survival differences, thus highlighting its essential value.